A Survey of Simulation Utilization in Anesthesiology Residency Programs in the United States. Issue 11 (1st June 2016) - Rochlen, Lauryn R.; Housey, Michelle; Gannon, Ian; Tait, Alan R.; Naughton, Norah; Kheterpal, Sachin
Abstract : Given the evolution of competency-based education and evidence supporting the benefits of incorporating simulation into anesthesiology residency training, simulation will likely play an important role in the training and assessment of anesthesiology residents. Currently, there are little data available regarding the current status of simulation-based curricula across US residency programs. In this study, we assessed simulation-based training and assessment in US anesthesiology programs using a survey designed to elicit information regarding the type, frequency, and content of the simulation courses offered at the 132 Accreditation Council of Graduate Medical Education-certified anesthesiology training programs. The response rate for the survey was 66%. Although most of the responding programs offered simulation-based courses for interns and residents and during CA-1 orientation, the curriculum varied greatly among programs. Approximately 40% of responding programs use simulation for resident assessment and remediation. The majority of responding programs favored standard simulation-based training as part of residency training (89%), and the most common perceived obstacles to doing so were time, money, and human resources. The results from this survey highlight that there are currently large variations in simulation-based training and assessment among training programs. It also confirms that many program directors feel that standardizing some components of simulation-based education and assessment would be beneficial. Given the positive impact simulation has on skill retention and operating room preparedness, it may be worthwhile to consider developing a standard curriculum.